Acta Medica Indonesiana - The Indonesian Journal of Internal Medicine 153 Malignant Pleural Effusion in Acute Myeloid Leukemia with Hepatitis B Virus Infection - C Suharti; Santosa, Santosa,; Budi Setiawan (Acta Medica Indonesiana)
Pleural effusions can be the first presentation of a hematologic malignancy. The most common disorders with pleural effusion are Hodgkin and non-Hodgkin lymphoma with a frequency of 20 to 30%, especially if mediastinal involvement. Acute and chronic leukemia are rarely accompanied by pleural involvement. We describe a 46-year-old female with history of progressive dyspnoea. Physical examination was revealed massive left pleural effusion. Complete blood count revealed anemia, trombositopenia and normal leucocyte count. Viral serology test shown positive of HBsAg and total antiHBc. Chest X-ray revealed left pleural effusion. Pleural fluid cytology was myeloblast consistent with acute myeloid leukemia (AML). Bone marrow aspiration smear, bone marrow biopsy smear, and flow cytometry analysis were consistent with acute myeloid leukemia without maturation (AML M0-FAB classification).